Employee Performance Model Through Job Satisfaction: Knowledge Management, Career Development and Motivation at PT Home Credit West Sumatera - Marta Widian Sari; Vivi Nila Sari; Moren Yohana (Journal of Accounting and Finance Management, 2022)
This study aims to examine the effect of Knowledge Management, Career Development, and Motivation on Employee Performance with Job Satisfaction as an Intervening Variable at PT. Home Credit Indonesia West Sumatra. By using primary data obtained by collecting questionnaires with a sample of 38 respondents from employees of PT. Home Credit Indonesia, West Sumatra. The method used in this research is Structural Equation Modeling Analysis with Partial Least Square (PLS).The results of this study conclude that: (1) knowledge management has a positive and significant effect on job satisfaction. (2) career development has no positive and significant effect on job satisfaction. (3) motivation has a positive and significant effect on job satisfaction. (4) knowledge management has no positive and significant effect on job satisfaction. (5) career development has a positive and significant effect on employee performance. (6) motivation has no positive and significant effect on employee performance. (7) job satisfaction has a positive and significant effect on employee performance. (8) knowledge management has a positive and significant effect on employee performance through job satisfaction. (9) career development has no positive and significant effect on employee performance through job satisfaction. (10) motivation has a positive and significant effect on employee performance through job satisfaction.